Does Distance Determine Who Attends a University in Germany? - C. Katharina Spieß; Katharina Wrohlich (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We analyze the role of distance from a university in the decision to attend higher education in Germany. Students who live near a university can avoid moving and the increased living expenses by commuting. Thus, transaction cost arguments would suggest that the greater the distance to the nearest university, the lower the participation in higher education. We analyse this hypothesis by combining data from the German Socio-Economic Panel Study (SOEP) with a database from the German Rectors' Conference on university postal codes. Based on a discrete time hazard rate model we show that distance to the next university at the time of completing high school significantly affects the decision to enrol in tertiary education. Controlling for many other socio-economic and regional variables, we find that 1 kilometre distance decreases the probability to enrol in higher education by 0.2 - 0.3 percentage points
Keywords: I2; R1; 330; Higher education; distance to university; competing risk model